Brown girls - Andreades, Daphne Palasi (New York : Random House, 2022)
A coming-of-age novel that follows a group of young women of color growing up in Queens, New York, as they navigate identity, community, and belonging.
Originally published in hardcover by Random House in 2022.
Keywords: Young women -- Fiction; Women -- New York (State) -- Queens -- Fiction; Immigrants -- New York (State) -- Queens -- Fiction; Identity (Psychology) -- Fiction; Queens (New York, N.Y.) -- Fiction